1990
DOI: 10.1002/clc.4960130311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical approach to paroxysmal atrial fibrillation

Abstract: Summary: In addition to the role of the electrophysiological substrate, paroxysmal atrial fibrillation depends on the modulation of the atrial tissues by the autonomic nervous system. Experimentally, models of atrial fibrillation can be based on either adrenergic or vagal stimulations that provoke the arrhythmia by disturbing in a different way conduction and refractory periods of the atrium. Clinically, the role of the autonomic nervous system can be suspected from the clinical history, and paroxysmal attacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
5

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 4 publications
0
28
0
5
Order By: Relevance
“…6 -10 The autonomic nervous system may play an important role as a trigger for the spontaneous onset of paroxysmal atrial fibrillation (AF). 11,12 However, only a few and partly controversial reports exist concerning changes in HR variability preceding the onset of AF. [13][14][15][16] A recent study suggested that altered complexity of R-R interval dynamics precedes the AF episodes of patients after coronary artery bypass graft surgery.…”
mentioning
confidence: 99%
“…6 -10 The autonomic nervous system may play an important role as a trigger for the spontaneous onset of paroxysmal atrial fibrillation (AF). 11,12 However, only a few and partly controversial reports exist concerning changes in HR variability preceding the onset of AF. [13][14][15][16] A recent study suggested that altered complexity of R-R interval dynamics precedes the AF episodes of patients after coronary artery bypass graft surgery.…”
mentioning
confidence: 99%
“…8 -10 Autonomic nervous system perturbations may enhance vulnerability to atrial arrhythmias. 5,[11][12][13][14] Analysis of HRV has been used to probe autonomic mechanisms of ventricular tachycardia and fibrillation and to identify patients at risk for ventricular arrhythmias. [15][16][17][18][19][20] Preliminary investigations in primarily nonsurgical populations have suggested that risk for AF may be identified with measurement of HRV, but whether the onset of postoperative AF is preceded by autonomic dysfunction is not clear.…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20] Preliminary investigations in primarily nonsurgical populations have suggested that risk for AF may be identified with measurement of HRV, but whether the onset of postoperative AF is preceded by autonomic dysfunction is not clear. 13,14,[21][22][23] Moreover, initial evaluations of HRV and AF risk have been limited to the usual time or frequency domain measures of HRV. 13,14,[21][22][23] Nonlinear methods of HRV analysis provide information about the dynamics of heart rate not evident with traditional methods of HRV measurement.…”
mentioning
confidence: 99%
“…У некоторых пациентов без структурных изменений сердца в тече-ние нескольких минут до развития ФП обнаруживали преобладание парасимпатического тонуса, в то время как у других отмечалось смещение баланса в сторону симпатической нервной системы [108,109]. У части па-циентов можно выделить вагальную или адренерги-ческую формы ФП [110]. ФП, опосредованная пара-симпатической активностью, обычно возникает ночью или после еды, в то время как адренергическая ФП в типичном случае развивается в дневное время [111].…”
Section: вегетативная нервная система и фибрилляция предсердийunclassified